A multi-criteria approach for selecting the seismic retrofit intervention for an existing structure accounting for expected losses and tax incentives in Italy. (1st November 2018) - Caterino, Nicola; Cosenza, Edoardo
Abstract: A multi-criteria decision tool to evaluate alternative seismic retrofit solutions for under-designed reinforced concrete (RC) structures is proposed herein. Besides structural performance, other criteria are evidently involved in such a choice, which deals with social and economic issues. In Italy, a recent law established significant tax incentives for those owners who decide to invest money for improving the structural safety of their buildings, with particular regard to earthquake resistance. The benefit is based on the classification of seismic risk of the construction prior to and after the intervention. It allows owners to recover up to 85% of the total expenses for retrofit, depending on the degree of improvement in the seismic classification as a result of the intervention. The seismic class is related to the expected annual losses, and it considers the most probable damages and repairing costs of structural and non-structural elements that are related to earthquakes and may occur during the economic life of the structure. This Italian legislative novelty is expected to make owners reconsider the convenience of performing seismic upgrade interventions. It will also influence the comparison of alternative interventions, as initial costs may play a secondary role in relation to what has been usual in the past. A framework for decision making on seismic retrofit is proposed. Its application to an RC-frame building, assumed as case study, is presented. Four different retrofit strategies (confinement of columns by glass fibre reinforced polymers, steel bracing, concrete jacketing of columns, and base isolation) are compared according to a set of criteria, including fiscal benefits. The discussion of the results highlights the main impact that the deductibility of intervention costs has on the decisions by owners.